2017
DOI: 10.1002/cm.21357
|View full text |Cite
|
Sign up to set email alerts
|

The rotation of mouse myoblast nuclei is dependent on substrate elasticity

Abstract: The complex interplay of biochemical signaling and mechanical traction forces regulate the position of cellular nuclei. Although the phenomenon of nuclear rotation has been observed for many years, the influence of substrate elasticity was unknown. We discovered another layer of complexity to this phenomenon: nuclear rotation is dependent on substrate elasticity. Nuclear rotation is drastically reduced on physiologically relevant stiffnesses. Here, we studied nuclear rotation in mouse C2C12 myoblasts cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
(211 reference statements)
0
7
0
Order By: Relevance
“…The basal layer is followed by the force transduction zone (cytoskeletal adaptors), and the upper most layer mediates the cytoskeleton regulatory protein connections (Kanchanawong et al, 2010). Evidently, the physical cues of the environment on the nanoscale elicit specific responses and dictate cellular function (Engler et al, 2004; Al-Rekabi and Pelling, 2013; Higuchi et al, 2013; Murray et al, 2014; Knight and Przyborski, 2015; Ravi et al, 2015; Hickey and Pelling, 2017) A schematic of the cell attachment is presented in Figure 1. Specifically, the topography, adhesion chemistry and localization, and mechanics play crucial roles in regulating cell fate and function (Harris et al, 1980; Dalby et al, 2002, 2007).…”
Section: Cellular Attachment At the Nanoscalementioning
confidence: 99%
“…The basal layer is followed by the force transduction zone (cytoskeletal adaptors), and the upper most layer mediates the cytoskeleton regulatory protein connections (Kanchanawong et al, 2010). Evidently, the physical cues of the environment on the nanoscale elicit specific responses and dictate cellular function (Engler et al, 2004; Al-Rekabi and Pelling, 2013; Higuchi et al, 2013; Murray et al, 2014; Knight and Przyborski, 2015; Ravi et al, 2015; Hickey and Pelling, 2017) A schematic of the cell attachment is presented in Figure 1. Specifically, the topography, adhesion chemistry and localization, and mechanics play crucial roles in regulating cell fate and function (Harris et al, 1980; Dalby et al, 2002, 2007).…”
Section: Cellular Attachment At the Nanoscalementioning
confidence: 99%
“…To increase the stability of the fabricated structures additional cross-linking would be an option. Studies have shown that gelatine scaffolds cross-linked with Glutaraldehyde and treated with sodium borohydride exhibit significantly increased stability, even in cell culture conditions (37 °C, 5% CO 2 ) and provide sufficient biocompatibility [11,12].…”
Section: Resultsmentioning
confidence: 99%
“…Two formulations were tested, the native untreated scaffolds as well as a group of chemically crosslinked scaffolds. To crosslink the samples with glutaraldehyde (GA) we adapted an approach described previously for similar protein based scaffolds [22,23] . A 0.5% GA solution was prepared from a 50% electron microscopy grade glutaraldehyde stock (Sigma) and diluted with PBS (Fisher).…”
Section: Bread Recipe and Fabricationmentioning
confidence: 99%